2010
DOI: 10.1002/cmdc.201000265
|View full text |Cite
|
Sign up to set email alerts
|

α‐Ketoheterocycles as Inhibitors of Leishmania mexicana Cysteine Protease CPB

Abstract: Cysteine proteases of the papain superfamily are present in nearly all eukaryotes and also play pivotal roles in the biology of parasites. Inhibition of cysteine proteases is emerging as an important strategy to combat parasitic diseases such as sleeping sickness, Chagas disease, and leishmaniasis. Inspired by the in vivo antiparasitic activity of the vinylsulfone-based cysteine protease inhibitors, a series of α-ketoheterocycles were developed as reversible inhibitors of a recombinant L. mexicana cysteine pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 61 publications
1
22
0
1
Order By: Relevance
“…Other cysteine protease inhibitors from natural resources, such as plant cystatins, or chemically synthetized, such as pseudopeptide substrate analogues, derivatives of aziridine, triazoles, -ketoheterocycles and NO-donors, were assayed against Leishmania. These compounds provided different degrees of inhibition in promastigote growth and viability, amastigote survival and reduction in the macrophages infection rate (Duboise et al, 1994;Pral et al, 1996;Alves et al, 2001;Tornøe et al, 2004;Ascenzi et al, www.intechopen.com Schurigt et al, 2010;Steert et al, 2010). Although cysteine proteases inhibitors look promising, the activity of the three cysteine proteases families would need to be blocked to completely prevent parasite invasion or replication in the host cells and lesion development, and non-selective inhibitors can also affect the host cysteine proteases.…”
Section: Cysteine Proteasesmentioning
confidence: 99%
“…Other cysteine protease inhibitors from natural resources, such as plant cystatins, or chemically synthetized, such as pseudopeptide substrate analogues, derivatives of aziridine, triazoles, -ketoheterocycles and NO-donors, were assayed against Leishmania. These compounds provided different degrees of inhibition in promastigote growth and viability, amastigote survival and reduction in the macrophages infection rate (Duboise et al, 1994;Pral et al, 1996;Alves et al, 2001;Tornøe et al, 2004;Ascenzi et al, www.intechopen.com Schurigt et al, 2010;Steert et al, 2010). Although cysteine proteases inhibitors look promising, the activity of the three cysteine proteases families would need to be blocked to completely prevent parasite invasion or replication in the host cells and lesion development, and non-selective inhibitors can also affect the host cysteine proteases.…”
Section: Cysteine Proteasesmentioning
confidence: 99%
“…The recombinant cathespin L-like rCPB2.8 from L. mexicana is an isoform without the C-terminal extension that has been used as target in the search for new leishmanicidal compounds (Alves et al, 2001;Desai et al, 2006;Gontijo et al, 2012;Judice et al, 2013;Schröder et al, 2013;Steert et al, 2010). The structure of this enzyme has the amino acid residues Asn 60 , Asp 61 and Asp 64 in the α-helices (wall of the active site), and previous NMR experiments revealed that rCPB2.8 adopts a type of immunoglobulin-like fold (Juliano et al, 2004;Smith et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme concentration determined by active site titration with E-64 was found to be 6 μM. The portion of active enzyme recovered was approximately 30% of the total recombinant enzyme [25]. Bovine cathepsin B (BtCatB, EC 3.4.22.1) was obtained from Sigma-Aldrich Inc., St. Louis, MO, USA.…”
Section: Methodsmentioning
confidence: 99%
“…Inhibitors containing a reversible reactive warhead-type might be expected to possess better safety profiles with regards to their potential application as drugs for treating parasitic infections, examples of such reactive inhibitors of L. mexicana CPB are compounds of the class of α-ketoheterocycles [25]. In order to identify new warhead-types that are reversibly reactive and have some specificity for cysteine proteases of trypanosomatid parasites, high throughput screening of a compound library against L. mexicana CPB2.8 and bovine cathepsin B as a counter assay was performed.…”
Section: Introductionmentioning
confidence: 99%